Qualitative lens to assessing the ground level implementation of conditional cash transfer scheme in India - Sharma, Shantanu; Mehra, Devika; Nayak, Harsavardhan; Singh, M. M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Conditional cash transfer scheme, known as Janani Suraksha Yojna (JSY) is an innovative concept on the lines of behavioral economics. The study aimed to investigate factors associated with effective implementation of scheme at the community in Delhi, India. Methods: We did qualitative study to investigate the implementation factors related to JSY by conducting in depth interviews with 50 mothers in a span of three months. All the interviews were conducted in local language (Hindi) by the principle investigator. The data were collected through semi-structured interviews, which were later transcribed and recorded in Microsoft-Excel sheet. The themes were developed inductively, meaning that they were anticipated from the design of interview, during literature review and deductively meaning that they were not anticipated during design of the interview. Results: The mean (±SD) age of the women was 25(±3.5) years. More than three-forth of the mothers were not aware of the JSY scheme. Most of the women claimed limited support from accredited social health activist at the time of delivery. Provision of respectful maternity care was poor with women reporting episodes of verbal abuses, and arrogant attitude of the staff. Issues in utilization of the scheme encountered in study were untimely disbursement of money, problems in the process of BPL cards formation, lack of awareness on the scheme, banking illiteracy etc. Conclusions: Amidst the wider geographic reach and accessibility of the scheme by the poor, there exists some barriers to its effective implementation and practical challenges, which need immediate addressal by program managers.